Explaining the experiences of nursing administrators, educators, and students about education process in the COVID-19 pandemic: a qualitative study - Zahra Farsi; Seyedeh Azam Sajadi; Effat Afaghi; Andrew Fournier; Shahla Aliyari; Yazdan Ahmadi; Ebrahim Hazrati (BMC, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) has severely influenced various aspects of human life, particularly education. This study aimed to explain the impact of the COVID-19 pandemic on nursing education from administrators, educators, and students' perspectives. Methods This qualitative study with a conventional content analysis approach was conducted from June to October 2020 at a nursing school in Tehran. Thirteen participants were enrolled using purposive sampling. Data collection was through in-depth and semi-structured interviews and continued until reaching data saturation. Nursing administrators, educators, and students constructed interviews to understand nursing education changes during the pandemic. All interviews were recorded, transcribed, reviewed, coded, and analyzed using the Graneheim and Lundman methods. Results Interviewed respondents included administrators and professors (n = 6) and nursing students (n = 7). The respondents reported five main topic areas: (1) safe management in ambiguous situations; (2) perceived situations; (3) adaptive coping; (4) educational facilitators and challenges, and (5) continuing education in an uncertain context. The central theme was "close conflict of education with COVID-19". Conclusions The current study noted instability and challenges placed on nursing education during the pandemic. Opportunities were addressed during the pandemic to improve the nursing training process using planning, scientific management, emerging technology, innovative educational opportunities, and comprehensive support from institutional stakeholders. Clear guidelines and recommendations are needed to ensure medical education safety during the pandemic.